Research progress and challenges of stem cell therapy for ischemic stroke - Cha, Zaihong; Qiao, Yisheng; Lu, Qixiong; Wang, Qiyang; Lu, Xiaoyang; Zhou, Hu; Li, Tao (Frontiers in Cell and Developmental Biology, 2024)
Ischemic stroke is a significant global cause of death and disability. Currently, treatment options for acute ischemic stroke are limited to intravenous thrombolysis and mechanical recanalization. Therefore, novel neuroprotective strategies are imperative. Stem cell transplantation possesses the capabilities of differentiation, proliferation, neuronal replacement, nerve pathway reconstruction, secretion of nerve growth factors, and enhancement of the microenvironment; thus, it is a potential therapeutic approach for ischemic stroke. In addition, the immunomodulatory function of stem cells and the combined treatment of stem cells and exosomes exhibit a favorable protective effect on brain injury and neurological dysfunction following stroke. Meanwhile, the theory of microbiota-gut-brain axis provides us with a novel perspective for comprehending and managing neurological diseases. Lastly, stem cell transplantation has demonstrated promising outcomes not only in treating ischemic stroke but also in dealing with other neurological disorders, such as brain tumors. Furthermore, challenges related to the tissue source, delivery method, immune response, and timing of transplantation still need to be addressed to optimize the treatment.